Is Ablation to Termination the Best Strategy for Ablation of Persistent Atrial Fibrillation?. (August 2015) - Lim, Han S.; Derval, Nicolas; Komatsu, Yuki; Zellerhoff, Stephan; Denis, Arnaud; Shah, Ashok J.; Sacher, Frédéric; Hocini, Mélèze; Jaïs, Pierre; Haïssaguerre, Michel
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.